WHEAT PROTEIN INCREASING THROUGH RADIATION TECHNOLOGIES (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
The effect of various doses of γ-irradiation on the biochemical composition of the nuclear fractions of wheat seedlings has been investigated. The research results indicate a direct dependence of changes in the biochemical composition of nuclear membranes and soluble nuclear fraction on the magnitude of the radiation dose. A change in the protein content in the fraction of the nuclear membrane and in the soluble nuclear fraction of the cell nuclei of the seedlings of irradiated seeds was observed. The data obtained indicate that ionizing radiation as a result of chain reactions changes the content of nuclear fractions, which in turn leads to a change and disruption of the functional ability of the nucleus.
Keywords: γ-irradiation; wheat seedlings; the composition of the nuclear membrane; the composition of the soluble nuclear fraction